2022
DOI: 10.1177/00219096221141359
|View full text |Cite
|
Sign up to set email alerts
|

The Psychological, Social, and Economic Impacts of COVID-19 on Nepali Migrant Workers

Abstract: The global pandemic impacted Asian migrant workers disproportionately. During the first COVID-19 nationwide lockdown, Nepali migrant workers faced many challenges due to widespread misconceptions of them being vectors of COVID-19. This research examines COVID-19 impacts on international and internal Nepali migrant workers. A national survey on the social, economic, and psychological challenges of returning Nepali migrant workers was administered online from 10 May to 20 July 2020. A total of 672 responses were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Nepali youth compelled to live and work in the crowded camps and workplaces without proper protective measures, they feel at risk (Mandal 2020e, Nepal et al, 2020. Despite their expectation of returning to their pre-pandemic employment, most of them lost their jobs and income sources due to COVID-19 restrictions (Ghimire et al, 2022). Internal migrant workers experienced negative changes in personal and family lives since the stay-at-home order.…”
Section: Discussionmentioning
confidence: 99%
“…Nepali youth compelled to live and work in the crowded camps and workplaces without proper protective measures, they feel at risk (Mandal 2020e, Nepal et al, 2020. Despite their expectation of returning to their pre-pandemic employment, most of them lost their jobs and income sources due to COVID-19 restrictions (Ghimire et al, 2022). Internal migrant workers experienced negative changes in personal and family lives since the stay-at-home order.…”
Section: Discussionmentioning
confidence: 99%
“…Despite growing remittance and outgoing numbers, the COVID-19 pandemic has resulted in financial consequences for Nepali migrant workers. The personal economic impacts differed between international and internal Nepali migrant workers ( Ghimire, Nepal, Crowley, Ghimire, & Guragain, 2022 ). Ghimire et al ( Ghimire et al, 2022 ) found that internal Nepali migrant workers were almost 7 times more likely to plan to return to their current jobs following the lockdown and were 63% less likely to report that someone in their family lost a job due to the pandemic compared to international Nepali migrant workers.…”
Section: Introductionmentioning
confidence: 99%